Mechanical and thermal properties of graphene oxide reinforced acrylated epoxidised palm oil/unsaturated polyester resin - Nur Bazilah, Thalib (2021)
Palm oil has the potential to be a polymer resin to reduce the dependence on synthetic polymers. However, palm oil is a non -drying oil that is difficult to cure. This study was conducted to reduce the dependence on petroleum resources of synthetic polymers by mixing palm oil in synthetic polymer, unsaturated polyester (UPE) and reinforced with graphene oxide (GO) and cured by oven. In this thesis, the concentrations of epoxy acrylate palm oil (AEPO) were 10, 20 and 30 wt% and graphene oxide (GO) 0.03, 0.05, 0.07 and 0.1 phr, respectively. The effects of different AEPO and GO loading ratios in UPE/AEPO/GO composite mixtures were specifically studied for mechanical, morphological and thermal properties. Characteristic of UPE/EPO resins was performed using Fourier transform infrared spectroscopy (FTIR). Epoxy palm oil was activated by reaction with acrylic acid to form AEPO. The second step was to synthesize graphene oxide from graphite using a modified Hummer’s method. Graphite had undergone preoxidation before undergoing the oxidation process. The resulting graphite oxide was sonicated to separate graphite into GO flakes. The characteristics of the synthesized AEPO, GO and the interaction between UPE/AEPO/GO composites were studied through Fourier transform infrared spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR). Mechanical properties were studied through tensile strength, Young’s modulus, elongation at break and Izod impact test. The thermal properties of the samples were studied through Thermogravimetric Analysis (TGA) and Dynamic Mechanical Analysis (DMA). The morphology of the resin was studied through Scanning Electron Microscope (SEM). The C = C stretching confirmed the acrylate functional group versus to the EPO FTIR spectrum at wavenumber 1618 to 1635 cm-1. The functional groups in graphene oxide such as carbonyl (C = O) and hydroxyl (-OH) were seen in the FTIR spectrum of GO at wavenumber 1767 cm-1 and 1324 cm-1. A successful AEPO bound to the UPE was confirmed when the C = O wavenumber shifts to a lower wavenumber than the original EPO FTIR spectrum. The UPE/AEPO blends showed weaker tensile strength than UPE. The addition of 0.1 phr GO to 10 % by weight AEPO increased the tensile strength and impact strength of the composite by 18.8 % and 48.10 %, respectively. SEM figure of 90/10/0.1 (UPE/AEPO/GO) composite shows a long and parallel scratch surface along with small voids and small white fragments showing homogeneous GO distribution. At 0.07 phr GO and 10 % by weight AEPO, Young’s modulus increased to 388 %. However, the elongation at break of the UPE/AEPO/GO resin mixture decreased. From the TGA results, the addition of 0.1 phr GO to 10 % by weight increased the major degradation of UPE by 15.5 ° C. It reflects higher thermal stability. From the DMA results, the storage modulus, the highest peak of the loss modulus and its temperature are lower than the original UPE. At 90/10/0.1 (UPE/AEPO/GO), the maximum loss modulus was 21.4 % which is higher than UPE/AEPO blends due to the higher GO thermal conductivity. The glass transition temperature (Tg) also occurs at temperatures higher than 0 phr GO and the wider tan δ peak explains the high cross -linking density in this composite. The results of this study can be concluded that the 90/10/0.1 (UPE/AEPO/GO) composite is a good mixture with the characteristics of balance of tensile strength, impact, modulus, elongation and thermal leading to application on home panel components, bicycles , furniture and home furnishings.